2022
DOI: 10.1093/infdis/jiac060
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell-Mediated Antibody-Dependent Cellular Cytotoxicity Against SARS-CoV-2 After Natural Infection Is More Potent Than After Vaccination

Abstract: We compared the ability of SARS-CoV2 Spike-specific antibodies to induce natural killer (NK) cell-mediated antibody dependent cellular cytotoxicity (ADCC) in patients with natural infection and vaccinated persons. Analyzing plasma samples from 39 COVID-19 patients and 11 vaccinated individuals, significant induction of ADCC could be observed over a period of more than three months in both vaccinated and recovered individuals. Although plasma antibody concentrations were lower in recovered patients, we found an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…However, the antibodies triggering ADCC were not the ones targeting the spike protein, the viral component used in many current vaccines. In fact, further experiments revealed that vaccination-induced antibodies targeting the spike protein poorly engaged natural killer cells, a result in line with a study showing that vaccination-induced antibodies are not as good at mediating ADCC compared to infection-induced antibodies ( Rieke et al, 2022 ). Fielding et al then went on to reveal that the antibodies involved in ADCC were those produced in reaction to other viral proteins expressed at the surface of infected cells.…”
supporting
confidence: 78%
“…However, the antibodies triggering ADCC were not the ones targeting the spike protein, the viral component used in many current vaccines. In fact, further experiments revealed that vaccination-induced antibodies targeting the spike protein poorly engaged natural killer cells, a result in line with a study showing that vaccination-induced antibodies are not as good at mediating ADCC compared to infection-induced antibodies ( Rieke et al, 2022 ). Fielding et al then went on to reveal that the antibodies involved in ADCC were those produced in reaction to other viral proteins expressed at the surface of infected cells.…”
supporting
confidence: 78%
“…COVID-19 vaccines in NHP ( 29 ) and humans ( 1 ) have reported important roles for both neutralizing and non-neutralizing antibodies in reducing viral infection and COVID-19 disease. Further investigation into the role of non-neutralizing antibody functions in protection, including ADCC are needed ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst these, NK cell mediated ADCC is the most potent and consistent. While VOC might escape neutralization by mutational changes in the receptor binding domains, NK cell mediated ADCC effector functions is more resilient and remain preserved across the variants [14][15][16][17] for longer periods 18 .…”
Section: Discussionmentioning
confidence: 99%